Within-individual design for assessing true individual responses in resistance training-induced muscle hypertrophy - Chaves, Talisson Santos; da Silva, Deivid Gomes; Lixandrão, Manoel Emílio; Libardi, Cleiton Augusto (Frontiers in Sports and Active Living, 2025)
Understanding interindividual variability in muscle hypertrophy in response to resistance training (RT) is a key focus of contemporary research. Common aims include identifying determinants of variability and recognizing individuals who do not respond to RT (i.e., non-responders). However, accurately identifying true individual responses (TIR) remains challenging due to the complex nature of muscle hypertrophy assessments. This complexity arises from distinguishing the TIR from natural variation in muscle mass over time and random measurement error in pre- and postintervention assessments. Existing studies have often overlooked this complexity, failing to employ experimental designs capable of isolating the TIR. Additionally, the reliance on random measurement error assessments based on group level data may not adequately capture the biological variation in muscle mass within individuals. In this context, we propose an experimental design based on unilateral, within-subject resistance training, capable of estimating biological variation in muscle mass and identifying TIR to RT-induced muscle hypertrophy. Additionally, we present an approach to effectively identify non-responders.